Rubella immunity among pregnant women aged 15–44 years, Namibia, 2010. (August 2016) - Jonas, Anna; Cardemil, Cristina V.; Beukes, Anita; Anderson, Raydel; Rota, Paul A.; Bankamp, Bettina; Gary, Howard E.; Sawadogo, Souleymane; Patel, Sadhna V.; Zeko, Sikota; Muroua, Clementine; Gaeb, Esegiel; et al.
Highlights: 15% of pregnant Namibian women are susceptible to rubella. Women from rural residences were more likely to be seronegative for rubella. The offspring of these women are at risk for congenital rubella syndrome (CRS). The introduction of rubella vaccine will help reduce the risk of rubella and CRS. Summary: Background: The level of rubella susceptibility among women of reproductive age in Namibia is unknown. Documenting the risk of rubella will help estimate the potential burden of disease in Namibian women and the risk of congenital rubella syndrome (CRS) in infants, and will guide strategies for the introduction of rubella vaccine. Methods: A total of 2044 serum samples from pregnant Namibian women aged 15–44 years were tested for rubella immunoglobulin G antibody; the samples were obtained during the 2010 National HIV Sentinel Survey. The proportion of women seropositive for rubella was determined by 5-year age strata, and factors associated with seropositivity were analyzed by logistic regression, including age, gravidity, HIV status, facility type, and urban/rural status. Results: Overall rubella seroprevalence was 85% (95% confidence interval (CI) 83–86%). Seroprevalence varied by age group (83–90%) and health district (71–100%). In the multivariable model, women from urban residences had higher odds of seropositivity as compared to women from rural residences (odds ratio 1.40, 95% CI 1.09–1.81). Conclusions: In the absence of a routine rubella immunization program, the high level of rubella seropositivity suggests rubella virus transmission in Namibia, yet 15% of pregnant Namibian women remain susceptible to rubella. The introduction of rubella vaccine will help reduce the risk of rubella in pregnant women and CRS in infants.